Protocatechuic Acid Attenuates Osteoclastogenesis by Downregulating JNK/c‐Fos/NFATc1 Signaling and Prevents Inflammatory Bone Loss in Mice. (20th January 2016) - Park, Sun‐Hyang; Kim, Ju‐Young; Cheon, Yoon‐Hee; Baek, Jong Min; Ahn, Sung‐Jun; Yoon, Kwon‐Ha; Lee, Myeung Su; Oh, Jaemin
Abstract : Protocatechuic acid (PCA) plays a critical role in nutritional metabolism; it is a major metabolite of anthocyanins, which are flavonoids with a range of health benefits. PCA has a variety of biological activities including anti‐oxidant, antiinflammatory, anti‐apoptosis, and anti‐microbial activities. However, the pharmacological effect of PCA, especially on osteoclastogenesis, remains unknown. We examined the effect of PCA on receptor activator of NF‐κB ligand (RANKL)‐induced osteoclast differentiation and bone resorption. PCA dose‐dependently inhibited RANKL‐induced osteoclast differentiation in mouse bone marrow macrophages (BMMs) and suppressed the bone‐resorbing activity of mature osteoclasts. At the molecular level, PCA suppressed RANKL‐induced phosphorylation of JNK among MAPKs only, without significantly affecting the early signaling pathway. PCA also suppressed RANKL‐stimulated expression of c‐Fos and nuclear factor of activated T cells c1 (NFATc1) at the mRNA and protein levels, without altering c‐Fos mRNA expression. Additionally, PCA down‐regulated the expression of downstream osteoclastogenesis‐related genes including β3‐integrin, DC‐STAMP, OC‐STAMP, Atp6v0d2, CTR, and CtsK . Mice treated with PCA efficiently recovered from lipopolysaccharide‐induced bone loss in vivo . Thus, PCA inhibits RANKL‐induced osteoclast differentiation and function by suppressing JNK signaling, c‐Fos stability, and expression of osteoclastic marker genes. These results suggest that PCA could be useful in treatment of inflammatory bone disorders. Copyright © 2016 John Wiley & Sons, Ltd.